2021
DOI: 10.1101/2021.05.25.445606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

spatzie: An R package for identifying significant transcription factor motif co-enrichment from enhancer-promoter interactions

Abstract: Genomic interactions provide important context to our understanding of the state of the genome. One question is whether specific transcription factor interactions give rise to genome organization. We introduce spatzie, an R package and a website that implements statistical tests for significant transcription factor motif cooperativity between enhancer-promoter interactions. We conducted controlled experiments under realistic simulated data from ChIP-seq to confirm spatzie is capable of discovering co-enriched … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated that enhancer-promoter interactions regulate target genes in the genome, and specific transcription factor cooperation offers the possibility to understand the cell-type specificity of genome interactions [46], of which Cicero, PEP, and the latest proposed Spatzie attempted to detect the transcription factor motif cooperativity between enhancer-promoter interactions [47][48][49]. To analyze whether the sequence-based features within identified chromatin loops, we first performed experiments using Spatzie where all identified chromatin loops were used in each cell line.…”
Section: Transcription Factor Motif Co-enrichment Across Different Ce...mentioning
confidence: 99%
“…Some studies have demonstrated that enhancer-promoter interactions regulate target genes in the genome, and specific transcription factor cooperation offers the possibility to understand the cell-type specificity of genome interactions [46], of which Cicero, PEP, and the latest proposed Spatzie attempted to detect the transcription factor motif cooperativity between enhancer-promoter interactions [47][48][49]. To analyze whether the sequence-based features within identified chromatin loops, we first performed experiments using Spatzie where all identified chromatin loops were used in each cell line.…”
Section: Transcription Factor Motif Co-enrichment Across Different Ce...mentioning
confidence: 99%